Utilizing Culturally Relevant Texts in the English Language Arts Classroom - Heabler, Savannah (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2022)
Maintaining students’ engagement and assessing their reading comprehension is very challenging. Today, students have a difficult time connecting what they learn in class with their daily lives based on the texts that have been commonly used for years in the classroom. English language arts teachers introduce students to characters that they believe their students will relate to, however, every student comes from different cultural, socioeconomic, and diverse backgrounds that need to be taken into account when choosing texts to read in class. This paper explains why culturally relevant texts are important for English language arts teachers to incorporate into their classrooms to help students remain engaged and strengthen their reading comprehension.